Counseling’s Impact on Reproductive-Aged Women Knowledge and Attitude at Andalas Health Center - Burhan, Ida Rahmah; Chaniago, YN Zuhal Chaisart; Abdillah, Khalisha Azzahra Pramesti; Zulviyanda, Zakiya; Triananda, Claudia; Zachraina, Rifvia Mustikaweni (Andalas Obstetrics And Gynecology Journal, 2025)
Background: Cervical cancer is the fourth most common cancer in women. In Indonesia cervical cancer is the second most common cancer among women, with 50% of women died from the disease. Prevention of cervical cancer can be done by regular screening. Therefore, a national strategy was made by the Ministry of Health to accelerate Indonesia’s progress towards the elimination of cervical cancer. The strategy was adapted in local community health center, including Andalas Health Center. Cervical cancer screening rate at Puskesmas Andalas remains inadequate with coverqge of only 1.23%. This study aimed to determine the general characteristics, evaluate the level of knowledge and attitude regarding cervical cancer screening test, and assess the impact of health promotion through counseling and SOSIALITA pocketbook on knowledge and attitude of reproductive-aged women in the working area of Andalas Health Care. Methods: This study is a pre-experimental study with one group pretest-posttest method with respondents of 25 reproductive-aged women in working area of Andalas Health Center. Results: 40% women of reproductive age are in late adulthood (36-45 years), 80% had a senior high school education, 92% are not working, and 96% are married. Most reproductive-aged women have low-level knowledge (48%) and negative attitude (76%). The results of the pretest and posttest regarding cervical cancer detection test showed an increase in high-level knowledge and positive attitude. Conclusion: There is a significant relationship between health counseling and SOSIALITA pocketbook and reproductive-aged women’s knowledge and attitude regarding cervical cancer early detection test (p<0.05) Keywords: cervical cancer, IVA test, HPV DNA test, early detection, reproductive health